PENGARUH METODE PEMBELAJARAN PREVIEW, QUESTION, READ, REFLECTION, RECITE DAN REVIEW (PQ4R) BERBANTUAN MEDIA BOOKLET TERHADAP HASIL BELAJAR SISWA PADA MATERI IKATAN KIMIA SISWA KELAS X SMA NEGERI 1 PENGKADAN KABUPATEN KAPUAS HULU - Darmawansyah Darmawansyah; Cawang Cawang; Rody Putra Sartika (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACT This study aimed to determine the effect of booklet-based on PQ4R learning method. Using quasi experimental method, as well as nonequivalent control group design, this study employed students of grade X as the samples (Grade XA as the control group and grade XB as the experiment group). They were selected by using purposive sampling technique. The data collection tools used were essay and interview. While the data collection technique employed were measurement and direct communication. The study revealed that the average posttest score of the experiment group was 83,68, while the average posttest score of the experiment group was 83,68. Hence the experiment group was distributively considered normal. The homogeneity test indicated that both groups were homogenous (sig value 0,0522>0,05). However, the hypothetical test of t independent sample with α=0,05 discovered T account of 2,960>560. This value indicated that there was a significant difference of students’ learning achievement by using booklet based PQ4R method and lecturing method in chemical bonding class at grade X of SMA Negeri 1 Pengkadan. The result of effect size value was 0,81 which entailed the highest level of the effect (28,20%).Keywords: Booklet, Learning achievement, Chemical bonding, Method of Preview, Question,Read, Reflection, Recite and Review (PQ4R)